2017
DOI: 10.1016/j.cgh.2016.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Psyllium Fiber Reduces Abdominal Pain in Children With Irritable Bowel Syndrome in a Randomized, Double-Blind Trial

Abstract: BACKGROUND & AIMS We sought to determine the efficacy of psyllium fiber treatment on abdominal pain and stool patterns in children with irritable bowel syndrome (IBS). We evaluated effects on breath hydrogen and methane production, gut permeability, and microbiome composition. We also investigated whether psychological characteristics of children or parents affected the response to treatment. METHODS We performed a randomized, double-blind trial of 103 children (mean age, 13 ± 3 y) with IBS seen at primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 38 publications
4
69
0
2
Order By: Relevance
“…This study utilized previously collected clinical study data from children with IBS. The participants’ data were collected from a total of four observational and interventional pediatric clinical trials conducted at Baylor College of Medicine and Texas Children’s Hospital in Houston, TX . One parent signed informed consent and the child provided assent prior to initiation of each study.…”
Section: Methodsmentioning
confidence: 99%
“…This study utilized previously collected clinical study data from children with IBS. The participants’ data were collected from a total of four observational and interventional pediatric clinical trials conducted at Baylor College of Medicine and Texas Children’s Hospital in Houston, TX . One parent signed informed consent and the child provided assent prior to initiation of each study.…”
Section: Methodsmentioning
confidence: 99%
“…One study found that VSL#3 improved GI symptoms 134 , while the other reported that a combination of three bifidobacteria resolved abdominal pain and improved quality of life to a greater extent than placebo 135 . On the other hand, psyllium fiber reduced pain episodes in an RCT enrolling children with IBS without altering the composition of the gut microbiota based on 16S ribosomal RNA analysis 136 .…”
Section: Functional Gi Disordersmentioning
confidence: 99%
“…These subtypes include constipation‐predominant (IBS‐C), diarrhea‐predominant (IBS‐D), mixed (IBS‐M), and unspecified IBS (IBS‐U) . The most common subtypes of IBS in the pediatric population are IBS‐C (43%–75%) and IBS‐U (0%–43%) …”
Section: Introductionmentioning
confidence: 99%